A Study on the Relationship between Differentiation of Self and Styles of Love - S Ghanaat Bajgirani; A Ghanbari Hashem Abadi; F zarif (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2013)
This research intended to investigate the relationship between differentiation of self and styles of love and to compare styles of love and differentiation of self among married men and women in the city of Mashhad.  Some 120 married persons who were selected as samples were tested. To compare differentiation of self: DSL Questionnaire was used and to compare styles of love, Stenberg’s triangular love scale was employed. Data were gathered through SPSS and meaningful test of correlation coefficient and were analyzed using comparison test of two independent average. Analysis of data showed that reverse significant correlation was found between sub-sales of passion, commitment and sub-sales of emotional reactivity, position, emotional cutoff and fusion with others were reported. In addition, the results revealed that there was a meaningful difference between reactive distancing of men and women including more reactive distancing among men. Analysis of data showed that there was not any significant difference among the rest of sub-scales.